The Impact of Advertising on The Behavior of The Romanian Consumer of Food Supplements - Bianca-Cristiana VOICU; Ionuț TĂNASE; Gheorghe ORZAN (Communications of International Proceedings, 2021)
Organizations use advertising, as well as other means of communication, to send messages that can get a response from the target audience, either behavioral or perceptual. Thus, advertising can be defined as a persuasive means of communication, which aims to change the attitude of its recipients, in order to purchase a particular product or service. We approached this topic given the importance of the influence that the advertising campaigns used by food supplement suppliers exert among Romanian consumers, on their attitude regarding the buying behavior of such products. The paper aims to investigate the impact that advertising campaigns used by food supplement providers have on consumer attitudes. The article presents the results of the research on the impact that the advertising campaigns used by the food supplement suppliers exert on the attitude of the Romanian consumers through the prism of their consumption behavior. Thus, a quantitative survey was conducted on a sample of 125 respondents, in which the questionnaire was used as a data collection tool. The results showed that most of the time the advertising campaigns used by food supplement providers have a direct effect on the consumption behavior of the target audience.
Keywords: Marketing Research; Advertising Campaigns; Food Supplements; Consumer Behavior; Advertising.